How Chinese Childcare Services Are Facing a Dilemma: A Study Based on Grounded Theory - Liwei Liu; Xinyu Gong; Yuxuan Chen; Yinguang Sun (SAGE Open)
The Chinese government has implemented several policies to promote the development of childcare services. However, Chinese childcare services are facing a dilemma rather than flourishing. Against this background, this study intends to reveal the development process of the Chinese childcare service from prosperity to stagnation, the dilemmas that arise during this process, and the reasons why they face these dilemmas. Based on the grounded theory methodology, we interviewed 13 childcare institutions in Wuhan, coded the data, and formed a theoretical framework. We found that childcare services have undergone four development stages: rise, face dilemmas, attempt to Re-Rise, and Prefer to Stable. During the development process, childcare services are faced with four dilemmas: the external dilemma of lacking support, the internal dilemma in operation, the teacher dilemma of low quality and high turnover, and the parent dilemma of demands that cannot be met. We analyzed the reasons behind these issues and proposed suggestions to help Chinese childcare services boom again.